GAMBARAN KADAR LEUKOSIT HARI KE 1 DAN HARI KE 3 - Maskanah -; Herniyatun -; Tri Sumarsih (Jurnal Ilmiah Kesehatan Keperawatan, 2014)
Currently, diarrhea is disease that remains a global healthproblem especially in developing countries. Diarrhea is a bowel movement thatis not normal or watery stool from with more frequency than usual. Diarrheathat cause infection increases white blood cells (leukocytes). Leukocytes tohelp fight infection in the body. This study is to know the difference betweenthe levels of leukocytes day one and day three of diarrhea patients in MelatiRoom RSUD Kebumen.This day uses the comparative method to the observationalapproach. Data analysis using descriptive analysis and bivariate analysis usingstatistical paired t test. Based on research conducted showed the averagelevels of leukocytes day one showed 16.236,15 mm3. Average levels ofleukocytes day three showed 11.964,23 mm3. On relationship with theduration of diarrhea leukocytes level in teaching the value of p: 0,012(<0,05). The results showed that the longer diarrhea leukocytes levelsbecame lower with an average reduction 4.271,923 mm3. Keywords:duration of diarrhea, levels of leukocyte